Sweeping adventures - Quak, Alyn Lin Hui (Nanyang Technological University, 2024)
Sweeping Adventures an interactive installation designed to infuse a sense of delight and childlike wonder into mundane household chores, particularly the act of sweeping with a broom. Rooted in the belief that playfulness and imagination can be rekindled in adults through interactive experiences, the installation transforms the ordinary into the extraordinary. By combining the physicality of sweeping with a multisensory and interactive digital experience, the installation bridges the gap between the routine and the extraordinary, encouraging participants to embrace a childlike sense of play.